Extending the Boundaries: Reframing “Entrepreneurship as Social Change” Through Feminist Perspectives - Calás, Marta B.; Smircich, Linda; Bourne, Kristina A. (Academy of Management Review, 2009)
We engage in a critical theoretical exercise to extend the boundaries of entrepreneurship theory and research by reframing “entrepreneurship as positive economic activity” to “entrepreneurship as social change.” Reframing entrepreneurship through feminist analytical lenses, we argue that more theoretical frameworks are needed for exploring the varieties of social change that entrepreneurship may bring about. We also discuss what difference this would make in extant entrepreneurship perspectives. Theoretically, methodologically, and analytically, such reframing is the main contribution of this paper.